A Comprehensive Comparison of the Efficacy and Tolerability of Racecadotril with Other Treatments of Acute Diarrhea in Adults - Fischbach, Wolfgang; Andresen, Viola; Eberlin, Marion; Mueck, Tobias; Layer, Peter (Frontiers in Medicine, 2016)
Racecadotril is a guideline-recommended treatment to alleviate symptoms of acute diarrhea. A systematic review of randomized studies was performed comparing efficacy and safety of treatment with racecadotril to that with placebo or active treatments in adults. In five double-blind studies, racecadotril and placebo had comparable tolerability but racecadotril was more effective. This was consistent across multiple efficacy parameters including duration of diarrhea, number of diarrheic stools, abdominal pain and meteorism; it was also consistent across countries in Africa, Asia and Europe. In six randomized studies in outpatients comparing racecadotril to loperamide, resolution of symptoms occurred with similar speed and efficacy; however, racecadotril treatment was associated with less rebound constipation and less abdominal discomfort. A seventh comparative study performed in geriatric nursing home residents reported a superior efficacy of racecadotril. In direct comparison with Saccharomyces boulardii treatment, racecadotril exhibited similar tolerability but was more efficacious. One study compared racecadotril to octreotide in patients with acute diarrhea requiring hospitalization, rehydration and antibiotic treatment; in this cohort, octreotide was more efficacious than racecadotril. In conclusion, in adults with acute diarrhea racecadotril is more efficacious than placebo or Saccharomyces boulardii, similarly efficacious as loperamide and, in patients with moderate to severe disease as add-on to antibiotics, less than octreotide. The tolerability of racecadotril is similar to that of placebo or Saccharomyces boulardii and better than that of loperamide, particularly with regard to risk of rebound constipation. Taken together these data demonstrate that racecadotril is a suitable treatment to alleviate symptoms of acute diarrhea in adults.